Analisis Penggunaan Hiponim dan Hipernim dalam Koran Riau Pos Edisi Agustus 2020 - Ameliyatun Hidayah, Suci; Nazirun, Nazirun (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
This research was motivated by hyponyms and hypernyms contained in the Riau Post Newspaper. A hyponym is a relation of meaning whose meaning is more solemn or whose meaning is considered part of another expression while a hypernym is a relation of meaning whose meaning is more general or whose meaning represents another expression. Formulate the problem in this study, namely, (1) how is the use of hyponyms in Riau Pos newspaper? (2) how is the use of hypernyms in Riau Pos newspaper? This study aims to (1) describe, analyze and interpret the use of hyponyms in Riau Pos newspaper (2) describe, analyze and interpret the use of hypernyms in Riau Pos newspaper. This type of research is qualitative research with content analysis methods. The theory used in semantic research from the books Chaer (2009), Djajasudarma (2012) and Tarigan (2009). The research approach is qualitative type library. The method used content analysis. The results of research from the analysis of the use of hyponyms and hypernyms in the Riau Pos newspaper are hyponyms there are 20 data, one of the data citations in which there is hyponymous data is "Indonesian technology company, Gojek officially integrates its application in three other countries, namely Vietnam, Singapore and Thailand". The word 'Vietnam, Singapore and Thailand' is a hyponymous data. Hypernym there are 14 data, one of the data quotes in which there is hypernym data is "The education sector in the village of Marga Mulya is quite advanced, because from all levels of education already exist, ranging from PAUD, KINDERGARTEN, ELEMENTARY, JUNIOR HIGH, HIGH SCHOOL, Ponpes and MDTA". The word education level is hypernymous data.